TALENT RETENTION CHALLENGES IN IT SECTOR OF INDIA - Harshita, SHRIMALI; Bhanupriya, KHATRI (Strategii Manageriale, 2015)
In current economy, HR leaders endorse the consideration of employees as their prime assets & foundation of their competitive advantage. In the competitive scenario, the volume of information has transferred the equilibrium of control in support of employees compared to employer.